Exciton-phonon coupling in individual ZnTe nanorods studied by resonant Raman spectroscopy - Zhang, Q. (2013)
The exciton-phonon coupling in high-quality cubic phase zinc telluride (ZnTe) nanorods (NRs) is investigated by resonant micro-Raman spectroscopy near the direct bandgap of ZnTe. The scattering cross section of longitudinal optical (LO) phonon is enhanced significantly in the resonant process, where the enhancement factor of LO modes is much higher than that of the transverse optical (TO) modes, indicating a dominant Fröhlich electron-phonon interaction mechanism. Up to fifth-order LO phonons are observed by resonant Raman scattering at room temperature. The Huang-Rhys factor of individual NRs—and thus the exciton-LO coupling strengths—is evaluated, showing increasing with the NR diameter. Surface optical (SO) phonon and its high-order overtones are observed between nLO and (n − 1)LO + TO for the first time, whose positions are consistent with a dielectric continuum model. Strong acoustic phonon-exciton coupling induces a high-frequency shoulder above each nLO peaks with two maxima located around 14 cm−1 and 32 cm−1, which are assigned to transverse acoustic and longitudinal acoustic phonons, respectively. The resonant multiphonon scattering process involving acoustic and LO phonons is discussed based on an exciton-intermediated cascade model, where a scattering sequence of acoustic phonon followed by LO phonons is favorable. These results advance the understanding of electron-phonon coupling and exciton scattering in quasi-one-dimensional systems, especially in the scarcely documented ZnTe compound, facilitating the development and optimization of NR-based optoelectronic devices.